Mental health related experiences among African Caribbean, and Black immigrant and refugee families living with HIV/ AIDS in Greater Toronto Area, Canada - Kamanzi, Joyce; Khanlou, Nazilla; Ongoiba, Fanta; Khan, Attia (INYI Journal, 2024)
Introduction: In 2021, there were nearly 38 million people living with HIV worldwide and approximately 61,110 in Canada. Africans, Caribbean people, and the Black community make up less than 3.5% of the Canadian population, but account for 22% of people living with HIV in Canada. Our study explores the mental health related experiences of African, Caribbean, Black immigrant families living with HIV in Canada’s Greater Toronto Area. Methods: A qualitative descriptive study was carried out between September, 2022 and December, 2023. Purposive sampling was used to select 20 participants, and semi-structured interviews were conducted. Content and thematic analyses of data were performed. Results: Participants ranged in age from 32 to 73 years, 60% were female, the majority had only completed college (65%), and most of them were not working. Three themes were identified: 1) HIV related struggles (neurocognitive impairment, HIV-related stigma and shame, racism and discrimination, and the impact of HIV-related stigma on mental health); 2) Systemic barriers (racism, stereotyping, systemic discrimination, employment and housing issues); and 3) social network building (isolation and solitude, disclosure dilemma). Discussion: Intersecting and complex factors associated with immigration and resettlement of African immigrants living with HIV affect their mental health and that of their families. Isolation and social exclusion are major stressors for these families, and their mental health is compromised by everyday encounters with systemic barriers. Conclusion: African immigrants and refugees living with HIV/AIDS experience mental health challenges related to co-morbidities caused by the HIV Virus. Integration of mental health services into HIV services would strengthen HIV prevention and care outcomes and improve access to mental health care. Keywords: Immigrants and refugees, HIV/AIDS, mental health, families, Canada.